Cognitive and Affective Aspects of Creative Option Generation in Everyday Life Situations - Schweizer, T. Sophie; Schmalenberger, Katja M.; Eisenlohr-Moul, Tory A.; Mojzisch, Andreas; Kaiser, Stefan; Funke, Joachim (Frontiers in Psychology, 2016)
Which factors influence a human being’s ability to develop new perspectives and be creative? This ability is pivotal for any context in which new cognitions are required, such as innovative endeavors in science and art, or psychotherapeutic settings. In this article we seek to bring together two research programs investigating the generation of creative options: On the one hand, research on option generation in the decision-making literature and, on the other hand, cognitive and clinical creativity research. Previous decision-making research has largely neglected the topic of generating creative options. Experiments typically provided participants with a clear set of options to choose from, but everyday life situations are less structured and allow countless ways to react. Before choosing an option, agents have to self-generate a set of options to choose from. Such option generation processes have only recently moved to the center of attention. The present study examines the creative quality of self-generated options in daily life situations. A student sample (N = 48) generated options for action in 70 shortly described everyday life scenarios. We rated the quality of the options on three dimensions of creativity- originality, feasibility, and divergence - and linked these qualities to option generation fluency (speed and number of generated options), situational features like the familiarity and the affective valence of the situation in which the options were generated, and trait measures of cognitive performance. We found that when situations were familiar to the participant, greater negative affective valence of the situation was associated with more originality and divergence of generated options. We also found that a higher option generation fluency was associated with a greater maximal originality of options. We complete our article with a joint research agenda for researchers in the decision-making field focusing on option generation and on the other hand researchers working on the cognitive and clinical aspects of creativity.